Efeito dos sistemas de plantio, exclusivo e consorciado, na incidência e controle de ervas daninhas - Rezende, Gilson de Oliveira (1986)
An experiment was conducted to determine the influence of cropping systems and weedig levels in the behavior of field crops at the " Lavoura Seca" Experimental farm of the Federal University of Ceara, in Quixadá, Ceara, Brazil, in 1985. Sesame, corn, grain sorghum, and cowpea sole crops and cowpea intercroppedwith each of the other crops, subjected, to hoeing at 15, 30 and 45 days after seedling emergence, were tested [...]